Leaves of Populus nigra L. as bioindicator of heavy metal pollution; Проблемы геологии и освоения недр; Т. 2 - Yalaltdinova A. R. Albina Rashidovna (Geology, mining and petroleum engineering, 2013)
Заглавие с экрана